The Impact of Service Quality and Ease of Use on Customer Loyalty for BRILink in Pekanbaru City with Customer Satisfaction as a Mediating Variable - Alfath, Sauli; Jushermi, Jushermi; Noviasari, Henni (West Science Business and Management, 2024)
This research aims to determine the effect of service quality and ease of use on customer loyalty using BRILink services in Pekanbaru city with customer satisfaction as a mediating variable. The research population is customers at BRILink agents in Pekanbaru City who have made transactions more than once at the same outlet in Pekanbaru City, the number of which is unknown with a sample size of 120 respondents. Sampling used probability sampling techniques. Research data was collected using questionnaires. In terms of data analysis, this research used Structural Equation Modeling (SEM) analysis with Smart Partial Least Squares (SPLS) Version 3.0. The research results show that service quality and ease of use have a positive and significant effect on customer satisfaction, service quality and ease of use have a positive and significant effect on customer loyalty, customer satisfaction has a positive effect on customer loyalty, service quality and ease of use have a positive and significant effect on customer loyalty which is mediated by customer satisfaction among BRILink users in the city of Pekanbaru.